2017
DOI: 10.1016/j.coldregions.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Observation of microstructures of atmospheric ice using a new replica technique

Abstract: A replication technique has been developped to study the microstructure of atmospheric ice based on the use of nail varnish rather than more harmful materials. The potential of the technique was demonstrated by obtaining and reporting microstructures for impact ice grown on metal surfaces in an icing tunnel under a range of cloud conditions. The technique reveals grain structure, growth striations, porosity and etch features which may indicate an aspect of crystalographic orientations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…It was implied that the air solubility and rapid freezing rates were responsible for the formation of mini bubbles in the atmospheric ice. In addition, the microbubbles were responsible for the appearance and types of ice due to the light scatted and refracted in the bubbles with suited diameters [10]. As illustrated in Figure 7, the microbubbles conspicuously dominated the opaque appearance of the rime ice.…”
Section: Air Bubblesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was implied that the air solubility and rapid freezing rates were responsible for the formation of mini bubbles in the atmospheric ice. In addition, the microbubbles were responsible for the appearance and types of ice due to the light scatted and refracted in the bubbles with suited diameters [10]. As illustrated in Figure 7, the microbubbles conspicuously dominated the opaque appearance of the rime ice.…”
Section: Air Bubblesmentioning
confidence: 99%
“…However, compared to ice which has abundant reserves and can be regularly sampled, atmospheric ice, usually assembled on aircraft wings, cables, and blades, is much more difficult to acquire and characterize. Moreover, there are still many difficulties in handling such a material which is easily broken and modified by a slight change in temperature [10]. Despite centuries of exploration, which has been focused on atmospheric ice, a detailed and in-depth understanding of ice microstructures is still lacking [19].…”
Section: Introductionmentioning
confidence: 99%
“…Even if ideal bubble-free interfaces were achieved, microscopic crystal boundaries could be defects where potential crack initiation may take place [22][23] [24][25]. Experiments have shown that icing conditions influence grain sizes and thus their boundaries [26]. In addition to this, surface conditions of substrates varied from test to test, which can be another reason for inconsistent results of shear strength [11][27].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…The use of a g as the representative lengthscale with which to define the shear strength is justified on the grounds that, give that ice is brittle material, the grain size is expected to control the initial crack size and the separation between defects [21][22][23][24]. In the following results, the average grain size was obtained from measurement using a nail varnish replica method [25].…”
Section: Iicmentioning
confidence: 99%